Hospital network and access to Night and Holiday Patient Care - Celejewski, Michał; Pawlikowski, Jakub (Polish Journal of Public Health, 2018)
Night and Holiday Patient Care is a place providing health services, necessary for securing patients’ medical needs in efficient way and round-the-clock. Units providing such care are located in selected hospitals chosen in connection with the introduction of the hospital network since October 1, 2017. The main aim of the study was comparison of changes that occurred in the area of location and access to Night and Holiday Patient Care after and before establishing hospital network. The analysis was based on a review of the relevant legal acts available on the ISAP website, scientific articles selected from the medical databases, as well as information published on the official websites of governmental agencies and entities offering night and holiday medical services. The introduction of the hospital network has changed the number, localization and availability of places providing Nights and Holiday Patient Care. These changes resulted in, on the one side, faster access to more specialized medical care, on the other, a reduction in the number of places in some cities. These changes require monitoring in terms of access and quality of basic care services during nights and holidays, so that in the long-term it can be determined whether the applied changes were beneficial from the perspective of the patient and the health care system.